Twelve-month outcomes in overweight/obese users with mental disorders following a multi-element treatment including diet, physical activity, and positive thinking: The real-world “An Apple a Day” controlled trial - Giusti, Laura; Bianchini, Valeria; Aggio, Annalisa; Mammarella, Silvia; Salza, Anna; Necozione, Stefano; Alunno, Alessia; Ferri, Claudio; Casacchia, Massimo; Roncone, Rita (Frontiers in Psychiatry, 2022)
The present study aimed to evaluate the 12-month effectiveness of a real-world weight loss transdiagnostic intervention in overweight/obese participants affected by mental disorders under psychopharmacological treatment. We conducted a real-world, controlled, pragmatic outpatient trial. We allocated 58 overweight/obese adults under psychopharmacological treatment from a mental health outpatient unit and 48 overweight/obese adults from a cardiovascular prevention outpatient unit, and assigned them to an intervention or treatment usual as condition (TAU) enriched by life-style advice. Participants in both intervention groups took part in a diet programme (the modified OMNIHeart dietary protocol) and monitoring of regular aerobic activity. A brief group programme (“An Apple a Day” Metacognitive Training, Apple-MCT) was added in the intervention group of participants affected by mental disorders. The primary outcome was weight loss. Secondary outcomes included anthropometric, clinical, and metabolic variables. Psychopathology and health-related quality of life were also evaluated in the psychiatric sample. At 12 months, both intervention groups showed a more marked mean decrease in weight (6.7 kg, SD: 3.57) than the TAU group (0.32 kg, SD: 1.96), and a statistically significant improvement in metabolic variables compared with the control groups. Furthermore, the participants affected by mental disorders included in the intervention group reported improved health-related quality of life. Our findings suggest the need to implement integrated interventions based on a dietary protocol, physical activity, and modification of cognitive style in overweight/obese users with mental disorders.